Policy facilitators and barriers to the implementation of the ‘One Health’ approach in India: Placing One Health at the heart of COVID-19 recovery and beyond - Kashish Aneja; Rituparna Padhy; Sam Halabi (CABI One Health, 2023)
Abstract The COVID-19 pandemic has underscored the necessity of adopting an integrated approach towards sustainably balancing the health of people, animals and ecosystems by promoting One Health. The authors analyse the legal and regulatory frameworks in India for their existing and future capacity to accommodate One Health-based policies. India has adopted several action plans, initiated multiple cross-ministry projects, and established institutional bodies during the COVID-19 pandemic to promote One Health. However, many of these were implemented piecemeal due to the federal structure in the country and the lack of adequate sustained inter-ministerial collaboration. The prevalent overtones of anthropocentric bias in the existing laws and policies adversely affect the potential of an effective One Health framework in the country as well. The authors highlight future considerations for India for placing One Health at the centre of legislation and policy making, and recommend both short-term and long-term measures that ought to be considered. One Health impact statement This article is an invited review article that illustrates how India is strategically placed for incorporating One Health in its policy making for pandemic preparedness and beyond. It underscores the urgency of examining certain future considerations for developing effective One Health-based governance and regulatory frameworks in the country.